A Summative Evaluation of a Food Safety Social Marketing Campaign "4‐Day Throw‐Away" Using Traditional and Social Media. Issue 3 (8th July 2013) - James, Katie J.; Albrecht, Julie A.; Litchfield, Ruth E.; Weishaar, Christopher A.
Abstract Foodborne illnesses remain a common problem in the United States. Focus group results indicated that lack of knowledge and improper handling of leftovers were common among food preparers in families with young children. The USDA‐recommended storage time for leftovers was used to develop and conduct a food safety social marketing campaign, 4 Day Throw Away using both traditional and social media. A procedural model for developing a theory‐based nutrition education intervention and the Health Belief Model were used to design, implement, and evaluate this campaign. The #4 mascot made numerous public appearances (in person and TV) to convey the 4 Day Throw Away message; 10000 magnets were distributed; and 500 posters with tear‐off note card were posted in the traditional campaign. Magnets and note card directed recipients to a website (4984 visits) with food safety information about leftovers. The social media campaign included 4 YouTube videos (11759 views); a Facebook page (166 users with over 21240 post views); and 51 followers on Twitter. The use of multiple media channels increased awareness and intention to change health behaviors especially among parents of children 10 and younger. Both traditional and social media methods in the 4 Day Throw Away campaign reached the intended audience suggesting that interventions using a mix of media channels broaden the reach and potential for intended behavior change.